Essays on fiscal deficit, debt and monetary policy: a nonlinear approach - Ahmed, Haydory Akbar (Kansas State University, 2017)
This essay empirically investigates the dynamics between government debt and budget deficits in the United States during a recession as opposed to an expansion. We use four different budget deficits definitions to develop a more comprehensive insight. We estimate a threshold VAR model on quarterly data from 1947: Q1 to 2016: Q3 on debt to GDP and budget deficits to GDP ratio for the United States. Specification test using LR test rejects the null for a linear VAR against nonlinear VAR. The nonlinear impulse responses indicate, with an increase to budget deficits to GDP ratio, government debt to GDP ratio rise faster during a recession as opposed to an expansion, and tend to move in a counter-cyclical manner with an increase in the output gap. We can thus infer that governments chose economic stability over fiscal balance during recessions. With an increase in government debt to GDP ratio, nonlinear impulse response show budget deficits to GDP ratio grow faster during an expansion as opposed to a recession and exhibit counter-cyclicality with an increase in the output gap. All four budget defi cits definitions depict similar pattern. Robustness check, using cyclically adjusted primary budget deficit published by the congressional Budget Office, also con rm the above findings. In this essay, we explore the presence of a long run relationship between the monetary base and the government debt using monthly data from 1942:1 to 2015:12. We apply formal statistical methods including cointegration and threshold cointegration tests to investigate the presence of a long-run relationship and estimate a threshold vector error-correction model (TVECM henceforth) to analyze the short-run dynamics. We find the presence of a threshold cointegration between the monetary base and government debt. As for the short-run dynamics, TVECM estimates show that the speed of adjustment is significant for the growth in debt equation in both regimes with the signs indicating government adjusting the debt in the short-run. But the U.S. Fed does not change the monetary base, hence we do not find any evidence of debt monetization in the U.S. We evaluate our findings over two sub-samples: 1946 to 2015 and 1946 to 2007 for robustness purposes. Findings from both sub-samples conform to our findings from the full sample. In this essay, we investigate the impacts of growth in the budget deficit and money supply on real interest rate are integral to contemporary macroeconomic policy. We employ threshold VAR and nonlinear impulse responses using quarterly data from 1959 to 2015. We find that growth in money supply and budget deficits have an asymmetric impact on inflation, short-term interest rate, and real interest rates. Growth in money supply and budget deficit tend to make the real interest rate negative in a bad state. In a good state, on the other hand, growth in money supply tend to increase the real interest rate but growth in budget deficits tend to decrease the real interest rate over the forecast horizon.
Keywords: Fiscal deficit; Debt; Monetary policy; Nonlinear times series; Threshold cointegration